Rafiki [videorecording (DVD)] - Kahiu, Wanuri; Mugatsia, Samantha; Munyiva, Sheila; Arac de Nyeko, Monica (Film Movement series., 2019)
Kena and Ziki have long been told that 'good Kenyan girls become good Kenyan wives,' but they yearn for something more. Despite the political rivalry between their families, the girls encourage each other to pursue their dreams in a conservative society. When love blossoms between them, Kena and Ziki must choose between happiness and safety.